2021
DOI: 10.3389/fmars.2020.606609
|View full text |Cite
|
Sign up to set email alerts
|

Small Cetacean in a Human High-Use Area: Trends in Harbor Porpoise Abundance in the North Sea Over Two Decades

Abstract: The North Sea is one of the most heavily used shelf regions worldwide with a diversity of human impacts, including shipping, pollution, fisheries, and offshore constructions. These stressors on the environment can have consequences for marine organisms, such as our study species, the harbor porpoise (Phocoena phocoena), which is regarded as a sentinel species and hence has a high conservation priority in the European Union (EU). As EU member states are obliged to monitor the population status, the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 109 publications
(173 reference statements)
1
15
0
1
Order By: Relevance
“…The rapid growth in the porpoise sighting and stranding rate in the southern North Sea has been reported extensively (Camphuysen, 2004;Hammond et al, 2013;Gilles et al, 2016;IJsseldijk et al, 2020;Nachtsheim et al, 2021). It has been suggested that this increase is linked to North Sea wide changes in prey distribution and abundance, although currently solid evidence is lacking (Camphuysen, 2004;Hammond et al, 2013).…”
Section: Variability In Strandings and Sightings In Relation To Phenologymentioning
confidence: 96%
See 3 more Smart Citations
“…The rapid growth in the porpoise sighting and stranding rate in the southern North Sea has been reported extensively (Camphuysen, 2004;Hammond et al, 2013;Gilles et al, 2016;IJsseldijk et al, 2020;Nachtsheim et al, 2021). It has been suggested that this increase is linked to North Sea wide changes in prey distribution and abundance, although currently solid evidence is lacking (Camphuysen, 2004;Hammond et al, 2013).…”
Section: Variability In Strandings and Sightings In Relation To Phenologymentioning
confidence: 96%
“…Apparently, porpoises move away from the nearshore regions out of sight from the Seabird watchers, who detect porpoises predominantly within 2 km from shore. These porpoises possibly move to nearby offshore waters (e.g., Geelhoed and Scheidat, 2018) or elsewhere (e.g., toward German and Danish waters) to give birth and nurse (Gilles et al, 2009;IJsseldijk et al, 2020;Nachtsheim et al, 2021). Porpoise coastal sighting rates slowly increases from August and into autumn.…”
Section: Variability In Strandings and Sightings In Relation To Phenologymentioning
confidence: 99%
See 2 more Smart Citations
“…Urbanization of the Salish Sea is likely one of the greatest contemporary threats to harbor porpoise in this region, as is the case in other areas. For example, declines in harbor porpoise abundance in parts of the well-studied North Sea over the last 20 years have been correlated with human highuse areas including activities like shipping, pollution, fisheries and offshore construction (Nachtsheim et al, 2021). Similarly, associated with urbanization of the Salish Sea is a myriad of vessel types ranging from recreational traffic, to essential services like ferries and the United States and Canadian Coast Guards, to the commercial economic livelihood sector including fishing, tourism (e.g., wildlife viewing and cruise ships), transportation of goods by ocean-going vessels, tug boats and barges, United States and Canadian national border services, research vessels, specialty services vessels (e.g., cable laying etc.)…”
Section: Knowledge Gaps and Threatsmentioning
confidence: 99%